Ibn Arabi on Wahdatul Wujud and it's Relation to The Concept of Af'alul 'Ibad - Dzulfikar Akbar Romadlon; Nur Hadi Ihsan; Istikomah Istikomah (Universitas Darussalam Gontor, 2020)
Abstract Wahdatul Wujud philosophy is said to have implications for Jabariyah understanding which resulted in the negation of the syari'at. This is because Wahdatul Wujud is understood to be the same as Pantheism. So this research aims to know the implications of Ibn 'Arabi's thought, known as Wahdatul Wujud, on Af'alul' Ibad discourse. This research is descriptive qualitative research using a literature study approach, the researcher will conduct a study of Ibn 'Arabi's works and some related literature. The conclusion of this study, when viewed from the concept of Wahdatul Wujud as believed by Ibn Arabi and his followers, shows that Ibn Arabi believes in the theory of kasb as believed by Imam Al-Ash'ari, that humans have a will to produce actions. However, the human will does not affect the actions. Because only Allah has the power to perform actions. This is consistent with the philosophy of Wahdatul Wujud, that there is no Being except Allah, meaning that there is no action in this world except the act of Allah. Human will and effort belong to man, but only Allah can make it happen. Based on this explanation, it can be concluded that Wahdatul Wujud does not affirm the Jabariyyah concept, which can result in the negation of the Shari'ah. Keywords: Ibn ‘Arabi, Wahdatul Wujud, human action, Allah knowledge.